Alcohol induced gelation of TEMPO-oxidized cellulose nanofibril dispersions12. Issue 45 (12th November 2018) - da Silva, Marcelo A.; Calabrese, Vincenzo; Schmitt, Julien; Celebi, Duygu; Scott, Janet L.; Edler, Karen J.
Abstract : Alcohol-induced gelation of partially oxidised cellulose nanofibrils (OCNFs): nanoscale (SAXS) and macroscale (rheology) insights into OCNF self-assembly in aqueous-alcoholic mixtures. Abstract : Solvent-induced physical hydrogels of TEMPO-oxidized cellulose nanofibrils (OCNFs) were obtained from aqueous/alcoholic dispersions of fibrils in lower alcohols, namely, methanol, ethanol, 1-propanol and 2-propanol. The sol–gel transition occurs above a critical alcohol concentration of ca. 30 wt% for all alcohols tested. The rheological properties of the hydrogels depend on the nature of the alcohol: for ethanol, 1-propanol and 2-propanol the magnitude of the shear storage modulus follows the alcohol hydrophilicity, whilst methanol produces the weakest gels in the group. Above a second critical concentration, ca. 60 wt% alcohol, phase separation is observed as the gels undergo syneresis. Analysis of small-angle X-ray scattering data shows that the OCNFs may be modelled as rigid rods. In the presence of lower alcohols, attractive interactions between nanofibrils are present and, above the alcohol concentration leading to gelation, an increase of the OCNF cross-section is observed, suggesting alcohol induced aggregation of nanofibrils.